Evaluation of the StrAli-BPM approach: strategic alignment with BPM using agreements in different levels. (2018) - Salles, Guilherme B.M.; Fantinato, Marcelo; Barros, Vitor Almeida; Albuquerque, João Porto De
Business process modelling languages do not usually represent non-functional requirements, focusing only on the functional ones. In order to fill this gap, the StrAli-BPM (strategic alignment with BPM) approach was presented. StrAli-BPM is divided in BLA@BPMN and BLA2SLA: the former extends BPMN to embody non-functional requirements through business level agreements (BLAs); the latter supports the creation of a set of service level agreements (SLAs) based on a particular BLA. This paper describes the results obtained with the evaluation of StrAli-BPM. The approach was evaluated by a proof of concept, based on prototype tools, which enabled us to verify its technical applicability. Moreover, a survey was conducted, in qualitative terms, with a panel of experts. As a result, StrAli-BPM was well accepted by the experts who judged it as important and necessary to completely cover the BPM lifecycle. Some lessons learned from both evaluations are presented.